Interventions in language acquisition and language competences in spanish-speaking children with a long hospital stay focused on english language. A scoping review (2021)
Table of contents 1. Research problem 6 1.1 Problem description 6 1.2 Problem formulation 7 2. Research Objectives 8 2.1 General Objective 8 2.2 Specific objectives 8 3. Justification and delimitation of the research 9 3.1 Justification 9 4. Reference framework 10 4.1 Theoretical framework 10 4.1.1 Long hospital stay. 10 4.1.2 Hospital Classrooms 12 4.1.3 Educational intervention 14 4.1.4 Learning 15 4.1.5 Education 16 4.1.6 Basic English learning rights for preschool, elementary and high school in Colombia17 4.1.7 Linguistic competence 19 4.1.8 Pragmatics 21 4.1.9 Sociolinguistic 22 4.2 Conceptual framework 24 4.3 Legal framework 27 5. Type of research 32 6. Methodology 33 6.1 Type of study 33 6.2 Population and sample 35 7. Sources of information 35 7.1. Primary sources 35 7.2. Secondary sources 36 8. Resources 36 8.1. Human resources 36 8.2. Physical resources 37 Page 4 de 57 8.3. Digital resources 37 9. Schedule 38 10. Results 42 Search flow and study characteristics 42 Which nursing interventions were identified? 42 Identification 43 Screening 43 Eligibility 43 Included 43 11. Discussion 45 12. Conclusion 50 13. Recommendations 50 14. Appendix A 50 15. References